Isolation and characterization of mutants of the RP4 plasmid coding for increased resistance to ampicillin - Cejka, K; Holubová, I; Hubácek, J; Navrátil, O; Braná, H (Folia microbiologica, 1985)
E. coli strain J53(RP4) was mutagenized with ethyl methanesulfonate and N-methyl-N'-nitro-N-nitrosoguanidine. Clones showing a two-to threefold increase in resistance to ampicillin were produced. This increase was not due to an increased number of RP4 copies per chromosome. The level of penicillinase activity was twice higher in comparison with the parental strain. No detectable changes were found in the region coding for the resistance to ampicillin on the plasmid by restriction analysis.
Keywords: replikace DNA; druhová specificita; Penicillin Resistance; Species Specificity; Ampicillin; ampicilin; Escherichia coli; R-plasmidy; mutace; ethylmethansulfonát; DNA Replication; DNA Restriction Enzymes; Mutation; restrikční enzymy; R Factors; Ethyl Methanesulfonate; rezistence na penicilin